2015
DOI: 10.5194/hess-19-1371-2015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying sensitivity to droughts – an experimental modeling approach

Abstract: Abstract. Meteorological droughts like those in summer 2003 or spring 2011 in Europe are expected to become more frequent in the future. Although the spatial extent of these drought events was large, not all regions were affected in the same way. Many catchments reacted strongly to the meteorological droughts showing low levels of streamflow and groundwater, while others hardly reacted. Also, the extent of the hydrological drought for specific catchments was different between these two historical events due to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 35 publications
7
34
1
Order By: Relevance
“…The correlation of the dependencies of summer low flows on catchment elevation can be explained by lower air temperature at higher elevation and thus more snow accumulation and may be supported by results of Birsan et al (2005) and Staudinger et al (2015) in Swiss catchments. Staudinger et al (2015) showed that higher-elevation and steeper catch- Figure 8.…”
Section: The Role Of Catchment Propertiesmentioning
confidence: 71%
See 2 more Smart Citations
“…The correlation of the dependencies of summer low flows on catchment elevation can be explained by lower air temperature at higher elevation and thus more snow accumulation and may be supported by results of Birsan et al (2005) and Staudinger et al (2015) in Swiss catchments. Staudinger et al (2015) showed that higher-elevation and steeper catch- Figure 8.…”
Section: The Role Of Catchment Propertiesmentioning
confidence: 71%
“…While meteorological drivers and overall catchment storage both affect the drought duration during summer, seasonal storage in snow and glaciers affect the drought deficit . However, snow cannot solely explain the sensitivity to drought, although higher-elevation catchments in the Swiss Alps were found to be less sensitive to drought origin (Staudinger et al, 2015). Additionally, some modelling experiments suggested larger groundwater storages in higher-elevation Swiss catchments which may additionally explain the lower sensitivity of higher-elevation catchments to low flows (Staudinger and Seibert, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the meteorological drought persists for a period of time, it will decrease the soil moisture and river flow, resulting in agricultural and hydrological droughts. Although the rainfall deficit is a primary driver for agricultural and hydrological droughts, terrestrial hydrological processes (e.g., snow melting, evapotranspiration) and geological and topographic conditions also play a nontrivial role in the drought propagation (Van Loon et al, 2012;Rimkus et al, 2013;Teuling et al, 2013;Stoelzle et al, 2014;Staudinger et al, 2015). Therefore, monitoring and forecasting of agricultural and hydrological droughts not only provide more relevant guidelines for the management of agricultural and water resources but also raise challenging scien-5478 X.…”
Section: Introductionmentioning
confidence: 99%
“…The differ-ent behavior can be directly related to the conceptual model complexity, discussed later. For the validation period 2011-2013, including a year with a long dry spell in spring 2011 (Staudinger et al 2015), differences in recharge occur for all simpler models, especially for the SWB and Finch model.…”
Section: Calibration Under Average Climatic Conditions and Validationmentioning
confidence: 99%